AUTOMATED LIVE AGRICULTURE MONITOR (ALAM) - Afifah Khairinniswah Tanjung; Muhammad Radhi Mudzakkir; Bukhari Farasdi Harahap; Rafa Ruzain Ahmad; Fathiyah Nurul Azizah Sinuhaji; Sandria Shelba Yafizham Harahap (RADJA PUBLIKA, 2026)
In order to assist precision agriculture and improve crop monitoring efficiency, we created the Automated Live Agriculture Monitor (ALAM), a web-based system that incorporates a wireless sensor network (WSN) and the Internet of Things (IoT). This system is intended to monitor critical plant and environmental factors such as temperature, air humidity, soil moisture, and light intensity in real time. Sensors located around the farms provide data to a central server via communication modules such as Wi-Fi on a regular basis, which subsequently visualizes the data using an interactive web interface. The acquired data is not only shown in real time, but it is also saved as historical data that may be studied later to aid agricultural decision-making, such as irrigation automation. Preliminary testing results show that the system performs consistently, with good measurement precision and data transfer dependability. With this approach, ALAM is projected to become a unique solution for efficient, smart, and sustainable crop monitoring, as well as a support for the agricultural sector's digitalization across several geographies.